Nest site charaderistics and reproductive success of burrowing owls (Strigiformes: Strigidae) in Durango, Mexico - Rodríguez-Estrella, Ricardo; Ortega-Rubio, Alfredo (Revista de Biología Tropical, 1993)
The burrowing owl, Athene cunicularia, is a threatened red species in most of its North American distributíon. Nest-site characteristícs and reproductive success were compared for two breeding seasons in the southem Chihuahuan desert, Durango, Mexico. Reproductive success is highly correlated with the presence of the ProsopisHilaria grassland association. The following factors were not associated with nesting success: burrow type, distance to the nearest adjacent nest, soil texture and number of perches.